A multivariate exploratory approach of the attributes of the visitors of Greek thermal springs by using a content management system. (2017) - Moschidis, Stratos; Tarnanidis, John
The purpose of this paper is to capture intense variations in service satisfaction with regard to the purpose of visiting the Greek thermal springs. The definition and the measurement of the quality of the services are important in this sector because it impacts in the general satisfaction. Thermal springs are an upcoming, mixed touristic product, used for healing or/and entertaining reasons. Therefore, we questioned a set of thermal springs' users and recorded their answers into variables that cover their personal, geographical, educational, economical profiles as well as their responses about thermal spring services. Data were collected through a Joomla content management system that implements access control list functionality and custom user fields. Next, data were processed with exploratory statistic analysis methods that find application space in exploratory holistic analysis in order to highlight the strongest trends in a phenomenon structure, especially when this has not been analysed before.